Analysis of Birth Weight and Birth Length with Stunting Incident in Children Aged 0-59 Months in Cinangka Depok - Ahid Nur Hidayati; Bagus Aprianto; Chahya Kharin Herbawani (Poltekkes Kemenkes Palu, 2022)
In Indonesia, the frequency of child stunting has remained high over the last decade, with an estimated 37 percent of children stunted at the national level. The prevalence of stunting in Depok accounted for 3.5% of the incidence of stunting, which means that as many as 3,675 of 105,127 children under five experienced stunting in Depok. Data from the Cinangka Primary Health Center, Depok, in 2022 showed 158 children experiencing stunting. This study aims to see whether there is a relationship between birth weight and body length with the frequency of stunting in children aged 0-59 months. With a cross-sectional study approach, primary data were obtained directly from 56 samples of children aged 0-59 months who were stunted by anthropometric examination and interviews with questionnaires. The analysis used Chi-Square statistical test. The result showed that the prevalence of stunting, low birth weight, and low birth length were 80.4%, 25%, and 48.2%. The study found no relationship between birth weight and birth length with the incidence of stunting in children aged 0 to 59 months at the Cinangka Primary Health Center, Depok. Stunting was caused by a complex set of circumstances that included not just the child's birth weight and length but also their nutritional intake, disease exposure, and therapy. The study's outcomes show that comprehensive treatments are needed to improve the stunting incidence in Cinangka Primary Health Center, Depok. Multilevel approaches should be used in interventions to address numerous elements at all levels, from the community to the individual